Effect of Sowing Dates on Growth, Yield and Quality Components of Bush Type Vegetable French Bean Varieties - Datta, Suchand; Sarkar, Ram Krishna; Rai, Ujyol (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted during the rabi season of 2017–18 and 2018–19 at Uttar Banga Krishi Vishwavidyalaya, Cooch Behar, West Bengal, India to study the effect of sowing time and variety on the growth, yield and quality of bush type vegetable French bean. The treatments were laid out in factorial randomised block design with three replications by keeping sowing time (S1: 1st November, S2:16th November, S3:1st December, S4: 16th December and S5: 31st December) as a first factor and varieties (V1: Falguni, V2: Arka Komal and V3: Nandini) as a second factor. Results revealed that, among the varieties the highest plant height (36.15 cm) , pod length (13.75 cm), pod width (1.13 cm), individual fresh pod weight (5.20 g), yield plant-1 (106.64 g) and yield ha-1 (16.36 t ha-1) was recorded in Arka Komal. However, the number of primary branches, number of pods plant-1 and protein content were found to be lowest in the same variety. Regarding the different sowing time, pod length (13.95 cm), individual fresh pod weight (5.47 g), number of pods per plant (27.64), yield plant-1 (136.22 g), yield per ha (20.86 t ha-1) and protein content (1.89%) was highest in plants sown on 16th November, per contra the yield curtailed as the sowing time was pushed back from 16th November to 31st December. On the strength of above findings, it can be inferred that Arka Komal scheduled for sowing on 16th November could be an ideal for cultivation in the Terai zone of West Bengal.